Online Learning Challenges in Academia: The Case of Uganda - Bwire, Felix; Bagarukayo, Emily; Birevu Muyinda, Paul (CSEDU, 2020)
Online learning is the access of learning experiences by the use of technology and internet, making the learning experience more convenient and accessible. Despite the wide adoption of Information and Communication technologies (ICT) in teaching and learning, ICT integration in teaching is still ad hoc and a lot more work has to be done to realize the full potential of online learning. This study was carried to establish the challenges that were hindering the wide adoption of online learning in universities in Uganda. It was discovered that internet connectivity and power supply were not reliable most especially in universities situated in rural areas. Teachers also lacked the required skills for designing online courses even in universities where infrastructure was not a problem. Therefore, we argue that for online learning to be widely adopted, teachers need to be adequately trained in online course design and mechanisms put in place to motivate the teachers to teach online.
Keywords: Online Learning; Learning Design